A Review on Formulation and Evaluation of Liposomal Drugs (British Journal of Multidisciplinary and Advanced Studies, 2023)
A liposome is the drug delivery system used for the administration of various types of drugs or active substances essential for the treatment of various types of diseases. They play a major role in the target delivery of the drug to particular tissue without affecting the other body parts. Hence it is also called targeted drug delivery system. The term liposome means lipid body. It has been derived on the basis of name of subcellular particles, ribosome. Liposomes were first made by the British scientist Alec Bangham and colleagues at Babraham Cambridge in the mid- 1960s and they first published the structure of liposomes in 1964.Their size ranges from 25 to 500 nm. In this present review, we discussed about liposomes formulation, evaluation and their mechanism of action in the biological system.